2006
DOI: 10.1136/bjo.2006.098111
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glaucoma using operator-dependent versus operator-independent classification in the Heidelberg retinal tomograph-III

Abstract: Objective: To compare the abilities of a new Glaucoma Probability Scoring (GPS) system and Moorfields regression analysis (MRA) to differentiate between glaucomatous and normal eyes using Heidelberg retinal tomograph (HRT)-III software and race-specific databases. Methods: In this prospective study, one eye (refractive error (5 D) each of consecutive normal patients and those with glaucoma was enrolled. All patients underwent a full eye examination, standard achromatic perimetry (Swedish Interactive Threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 14 publications
2
42
1
10
Order By: Relevance
“…These findings are similar with prior reports. 11,12 Zelefsky et al found no differences between HRT II and HRT 3 MRA in African and European ancestry groups. However, the authors found greater variation in sensitivity and specificity for subjects of African ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar with prior reports. 11,12 Zelefsky et al found no differences between HRT II and HRT 3 MRA in African and European ancestry groups. However, the authors found greater variation in sensitivity and specificity for subjects of African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies have shown similar to improved discriminatory ability of HRT 3 than HRT II. [11][12][13][14] Zelesfky et al found increased sensitivity in subjects with European and African ancestry using HRT 3. 11 These studies, however, were done with groups of glaucoma patients older than controls, the effect of age was not included, and racial comparisons were not performed.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the detection of glaucoma using optic disc analysis aims to reveal changes of the optic disc as being key criteria for glaucoma diagnosis. Harizman et al 34 recently published a study that evaluates the sensitivity of the Heidelberg Retina Tomograph III to detect glaucomatous optic disc damage in perimetric glaucoma. Sensitivity of the Moorfields regression analysis was 71.4 at 91.9% specificity.…”
Section: Eyementioning
confidence: 99%
“…GPS yöntemi iki adet parapapiller RSLT şekli ölçümü (yatay ve dikey RSLT eğriliği) ve üç adet OSB şeklini (çukurluk boyutu, çukurluk derinliği ve rim dikliği) kullanarak glokom olasılığını sınıflar (normal sınırlar içinde, sınırda ve normal sınırlar dışında). [6][7][8] GPS algoritması optik disk snırlarını belirleyen bir operatöre ve bir referans planına gerek duymadığından tanısal değerinin MRA'dan daha yüksek olması beklenebilir.…”
Section: Introductionunclassified